Structure-based virtual screening of dipeptidyl peptidase 4 inhibitors and their in vitro analysis. (April 2021) - Rahman, Shafiq Ur; Ali, Hafiz Saqib; Jafari, Behzad; Zaib, Sumera; Hameed, Abdul; Al-Kahraman, Yasser M.S.A; Langer, Peter; Iqbal, Jamshed
Graphical abstract: Structure-activity relationship of pyrazolo-pyridinol derivative (2 ) and thiadiazolo pyrimidinone derivative (13) with sitagliptin Highlights: Type 2 diabetes mellitus (T2DM) is widely prevalent metabolic disorder. Dipeptidyl Peptidase 4 (DPP-4) inhibitors are proven to be anti-diabetic drugs. The structure-based pharmacophore modeling has been employed. Virtual screening of compound library. In vitro assay and structure-activity relationship studies were carried out. Abstract: Type 2 diabetes mellitus (T2DM) is one of the most widely prevalent metabolic disorders with no cure to date thus remains the most challenging task in the current drug discovery. Therefore, the only strategy to control diabetes prevalence is to develop novel efficacious therapeutics. Dipeptidyl Peptidase 4 (DPP-4) inhibitors are currently used as anti-diabetic drugs for the inhibition of incretins. This study aims to construct the chemical feature based on pharmacophore models for dipeptidyl peptidase IV. The structure-based pharmacophore modeling has been employed to evaluate new inhibitors of DPP-4. A four-featured pharmacophore model was developed from crystal structure of DPP-4 enzyme with 4-(2-aminoethyl) benzenesulfonyl fluoride in its active site via pharmacophore constructing tool of Molecular Operating Environment (MOE) consisting F1 Hyd (hydrophobic region), F2 Hyd|Cat|Don (hydrophobic cationic and donor region), F3 Acc (acceptor region) and F4 Hyd (hydrophobic region). The generated pharmacophore model was used for virtual screening of in-house compound library (the available compounds which were used for initial screening to get the few compounds for the current studies). The resultant selected compounds, after virtual screening were further validated using in vitro assay. Furthermore, structure-activity relationship was carried out for the compounds possessing significant inhibition potential after docking studies. The binding free energy of analogs was evaluated via molecular mechanics generalized Born surface area (MM-GBSA) and Poisson-Boltzmann surface area (MM-PBSA) methods using AMBER 16 as a molecular dynamics (MD) simulation package. Based on potential findings, we report that selected candidates are more likely to be used as DPP-4 inhibitors or as starting leads for the development of novel and potent DPP-4 inhibitors.